Dynamic visual attention of elite table tennis players and boxers - Chiang, C.-H.; Liew, E.-W.; Song, T.-F.; Chen, W.-Y.; Wu, S. K. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
International Integrated Systems, Inc.Introduction: The ability to distribute the resources of attention is a crucial component for elite athletes` performance. Due to the specificity of the sport, certain abilities may be different between sports. Therefore, the purpose of this investigation was to analyze the dynamic visual attention among elite male collegiate table tennis (TT) players and boxers through multiple objects tracking task (MOT). Methods: We recruited 44 collegiate men including 11 TT players and 18 boxers in the national levels and 15 non-athlete men enrolled as the control group. All participants completed a series of MOT. We manipulated the velocities (0.6, 0.9, 1.2 r/s), target numbers (1 or 2), and the visual fields (unilateral or bilateral) of MOT. Four-way mixed ANOVA was used to analyze the correct rate of conditions between groups. Results: The result revealed that the main effects of target number (F(1,41)=125.48, p<0.05), visual field (F(1,41)=18.63, p<0.05) and velocity (F(1.71,69.92)=90.37, p<0.05) were significantly different. There was no significant difference between groups inmost conditions. However, the trend showed that correct rates of TT and boxers were slightly higher than non-athletes. Conclusion: According to the hemisphere-specific resource theory, this study found that elite athletes have better dynamic visual attention performance than the control group. Although there is no disparity between TT players and boxers, the future study may try to manipulate the difficulty of conditions to discriminate the ability of athletes in different sports.